Employment Rights in an Era of Individualised Employment - Anderson, Gordon (Victoria University of Wellington Law Review, 2007)
On 7 August 2007, Gordon Anderson delivered his inaugural lecture after becoming a professor in the Law Faculty of Victoria University of Wellington. Gordon took as his theme the protection of employees employed on an individual contract of employment. Following the repeal of the award system by the Employment Contracts Act 1991 the majority of New Zealand employees ceased to be covered by collectively negotiated instruments. Instead the contract of employment became dominant. The lecture argued that the common law contract of employment provides little protection for employees. Instead protection depends on some critical statutory interventions that provide a degree of balance within the employment relationship. While not perfect, these protections may be the best that can be expected in the real world of employment.